Are German Coaches Highly Exhausted? A Study of Differences in Personal and Environmental Factors. Issue 4 (August 2015) - Altfeld, Sebastian; Kellmann, Michael
Previous research has produced equivocal findings in regard to personal and environmental parameters influencing coaches' perceptions of stress and burnout levels. Moreover, there is a paucity of studies examining these factors in European professional sport contexts. This study investigated the influence of person-related (e.g., age, hours per week, level of recovery, coaching alternatives, experience as an assistant), sport-related (e.g., type of sport, working in youth or senior section, level of performing), and perception-related variables (e.g., feeling of meaningfulness, financial security) in relation to burnout of German full-time coaches. One-hundred and fifty eight coaches of different sports and levels completed a demographical survey, a German coaches' version of the Maslach Burnout Inventory, and the Recovery-Stress Questionnaire for Coaches. Two contrasting groups were formed to compare coaches with the lowest scores in Emotional Exhaustion (lowest 20%) and the highest scores in Emotional Exhaustion (highest 20%). Overall Stress (β = 3.92, p < .001) and Overall Recovery (β = −2.86, p < .001) demonstrated significant effects on Emotional Exhaustion within multiple regression analysis. Moreover, the variables sense of well-being ( r = −.46, p < .001), feeling of meaningfulness ( r = −.28, p < .001) showed significant relationships to the key burnout symptom of Emotional Exhaustion. The extreme group comparison indicated significant differences in person-related and perception-related parameters. Recovery as well as social support might be important in managing stress in the challenging work environments of full-time coaches. Additionally, the perception of the current coaching job might be more important than context-related variables (e.g., type of sport, level).